2017
DOI: 10.1080/15592294.2016.1277298
|View full text |Cite
|
Sign up to set email alerts
|

Fetal DNA hypermethylation in tight junction pathway is associated with neural tube defects: A genome-wide DNA methylation analysis

Abstract: Neural tube defects (NTDs) are a spectrum of severe congenital malformations of fusion failure of the neural tube during early embryogenesis. Evidence on aberrant DNA methylation in NTD development remains scarce, especially when exposure to environmental pollutant is taken into consideration. DNA methylation profiling was quantified using the Infinium HumanMethylation450 array in neural tissues from 10 NTD cases and 8 non-malformed controls (stage 1). Subsequent validation was performed using a Sequenom MassA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 49 publications
0
31
0
1
Order By: Relevance
“…Notably, emerging literatures have shown that 5hmC decrease is associated with human cancer and neural degenerative diseases [12,13]. Although there are several reports on aberrant dynamics of DNA methylation with NTDs [14][15][16][17][18], we are not aware of any studies that have explored the relationship between levels of 5hmC and NTDs, especially with environmental exposure being taken into consideration.…”
Section: Introductionmentioning
confidence: 96%
“…Notably, emerging literatures have shown that 5hmC decrease is associated with human cancer and neural degenerative diseases [12,13]. Although there are several reports on aberrant dynamics of DNA methylation with NTDs [14][15][16][17][18], we are not aware of any studies that have explored the relationship between levels of 5hmC and NTDs, especially with environmental exposure being taken into consideration.…”
Section: Introductionmentioning
confidence: 96%
“…In comparison to digital MS-HRM, which allows analysis only in limited compartments like in 96-reaction-well-plates, EAST-ddPCR can be performed in 20,000 up to several 10 6 compartments resulting in significantly higher analytical sensitivities and reproducibility. Sensitivity was determined below 1%, whereas other techniques like Next Generation Sequencing, Pyrosequencing, and SequenomMassArray exhibit sensitivities of 5-10%, also connected to high initial investment and consumable costs for the analysis of heterogeneously methylated epialleles (9,(12)(13)(14).…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, the analytical sensitivity and precision of this technique is limited. Other techniques, such as next generation sequencing, pyrosequencing and SequenomMassArray, are able to quantify heterogeneously methylated epialleles, but high upfront investment and consumable costs hinder their establishment in routine analytical laboratories (9,(12)(13)(14).…”
mentioning
confidence: 99%
“…A detailed description on the genome-wide methylation results obtained from Infinium HumanMethylation450 Bead-Chip (HM450K), using DNA isolated from neural tissues from ten NTD cases and eight unrelated non-malformed controls can be found elsewhere [23]. In brief, out of 485,199 CpG sites across the entire genome, 23,294 (4.8%) were differentially methylated between cases and controls.…”
Section: Methylation Of Pax3 Gene In Genomic Microarraymentioning
confidence: 99%